2010
DOI: 10.1227/neu.0b013e3181ecc49e
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Endothelial Progenitor Cells in the Human Brain and Spinal Cord Arteriovenous Malformations

Abstract: Objective-Brain and spinal cord arteriovenous malformations (AVMs) are characterized by aberrant angiogenesis and vascular remodeling. Endothelial progenitor cells (EPCs) can be recruited by stromal cell-derived factor-1 (SDF-1), and participate in vascular remodeling in both physiological and pathological settings. We hypothesized that there was increased EPC levels in the brain and spinal cord AVM nidus.Address correspondence to: William L. Young, MD, University of California, San Francisco, Department of An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…The role of BMDCs in sporadic brain AVM needs further study, as Mø are associated with the lesion 13 and EC precursors incorporate into the abnormal vascular structures. 14 Consideration should also be given to the role of endoglin in other cerebrovascular diseases such as stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The role of BMDCs in sporadic brain AVM needs further study, as Mø are associated with the lesion 13 and EC precursors incorporate into the abnormal vascular structures. 14 Consideration should also be given to the role of endoglin in other cerebrovascular diseases such as stroke.…”
Section: Discussionmentioning
confidence: 99%
“…BM-derived endothelial cells seed tumor vascular beds, regulating tumor angiogenesis [85, 86], and can incorporate into vessels in the brain angiogenic foci in mouse models [77, 78, 87]. In addition, endothelial cell progenitor cells have been identified in vessels in adult human sporadic bAVMs [88]. …”
Section: Brain Avm Pathogenesismentioning
confidence: 99%
“…For example, endothelial progenitor cells (EPCs) are present in the nidus of brain and spinal cord AVMs, and may mediate pathological vascular remodeling and impact the clinical course of AVMs. Gao et al demonstrated that both brain and spinal AVM tissues displayed more CD133, SDF-1, and CD68-positive signals than epilepsy and basilar artery control tissues [14]. EPCs, identified as CD133 and KDR double stained-positive cells, were increased in the brain and spinal cord AVM nidus, mainly at the edge of the vessel wall.…”
Section: Evidence For Abnormal Angiogenesis and Inflammation In Avmmentioning
confidence: 99%